ACADEMIC RESILIENCE AND STUDENTS ENGAGEMENT IN HIGHER EDUCATION: STUDY ON POST-PANDEMIC BEHAVIOUR - Sri Hardianti Sartika; Betanika Nila Nirbita (EDU SCIENCES JOURNAL, 2023)
The impact of the Covid-19 pandemic on the education sector is the closure of educational institutions globally and the change in learning methods to online learning. However, the government is currently re-implementing face-to-face learning to avoid learning in education. This transition phenomenon poses a challenge not only for lecturers but also for students, especially students who have been accustomed to doing online learning since they started college. Academic resilience and student engagement are two aspects that students need to adapt to learning during the transition from online learning to face-to-face learning. The focus of this research is to examine academic resilience and students' engagement in higher education during the transition period of existing learning methods. The research method used is descriptive quantitative, with 376 participants (23% male, 77% female) starting college in 2019-2022. The research instrument was adopted from the Academic Resilience Scale (ARS-30) and the Student Engagement Scale from Gunuc. The analysis results of academic resilience on perseverance, reflecting and adaptive help-seeking, and negative affect and emotional response in higher education on post-pandemic behavior at high criteria (78,70%). The analysis results of student engagement on emotional engagement, cognitive engagement, and campus engagement in higher education on post-pandemic behavior at high criteria (80,3%).